2022
DOI: 10.3390/ijerph19031215
|View full text |Cite
|
Sign up to set email alerts
|

Caries Risk Assessment Using the Caries Management by Risk Assessment (CAMBRA) Protocol among the General Population of Sakaka, Saudi Arabia—A Cross-Sectional Study

Abstract: Background: Caries risk assessment is a useful tool in caries prevention and management. Using a tool such as CAMBRA, every individual can be assessed according to his or her disease indicators, risk factors, and protective factors for the current and future caries. Aim: This study aimed to assess caries risk among the general population of Sakaka, Saudi Arabia using the CAMBRA protocol. Methods: This cross-sectional study was conducted at university dental clinics using a questionnaire that was formulated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In addition, 70.9% (Group I) and 60.3% (Group II) of the parents had nonskilled occupations. In fact, this finding was consistent with that of Iqbal et al ,[ 29 ] who found that 85% of their participants were at a high risk for caries and the remaining were at moderate risk. They attributed their results to the recruitment of the study sample from a dental department where most participants were seeking dental treatment and not routine care.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, 70.9% (Group I) and 60.3% (Group II) of the parents had nonskilled occupations. In fact, this finding was consistent with that of Iqbal et al ,[ 29 ] who found that 85% of their participants were at a high risk for caries and the remaining were at moderate risk. They attributed their results to the recruitment of the study sample from a dental department where most participants were seeking dental treatment and not routine care.…”
Section: Discussionsupporting
confidence: 92%
“…Dental caries is one of the commonest and perhaps most prevalent diseases affecting the oral cavity [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. It is a microbial disease of the calcified tissues of the teeth, characterized by demineralization of the inorganic component and destruction of the organic content of the tooth [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the severity of ECC between the ages of three and five, “dmf” ratings are used [ 1 ]. Numerous studies from the Kingdom of Saudi Arabia have reported a very high caries prevalence among preschool children [ 3 , 4 ]. Recent reports from Italy and Australia indicated unequal distributions in caries prevalence among preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…The preventive measures showed greater effectiveness on the smooth surfaces of the teeth while caries on occlusal surfaces remain a problem. The occlusal or so-called hidden caries usually get missed during visual examination because, in many cases, it lacks the typical cavity design in enamel, and a radiograph and a fissure biopsy are needed for its detection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%